2022
DOI: 10.1007/s00125-022-05654-0
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines induce rapid, NO-independent apoptosis, expression of chemotactic mediators and interleukin-32 secretion in human pluripotent stem cell-derived beta cells

Abstract: Aims/hypothesis The aim of this study was to examine the effects of proinflammatory cytokines on cells of different developmental stages during the generation of stem cell-derived beta cells (SC-beta cells) from human pluripotent stem cells (hPSCs). We wanted to find out to what extent human SC-beta cells are suitable as an experimental cellular model and, with regard to a possible therapeutic use, whether SC-beta cells have a comparable vulnerability to cytokines as bona fide beta cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…As expected, PDX1 expression was higher in -like cells, while Aristaless Related Homeobox (ARX), a transcription factor specifically expressed in glucagon-producing  cells, was much higher in -like cells. -Like cells had higher expression of the proapoptotic ER stress marker DDIT3 (also known as CHOP) [log 2 fold change (log 2 FC) = 2.20, adjusted P << 0.0001] and also XBP1 (log 2 FC = 0.70, adjusted P << 0.0001) [in line with (32)], while -like cells showed higher expression of the protective chaperone HSPA5 (also known as BiP) (log 2 FC = 0.13, adjusted P << 0.0001). Compared to -like cells, -like cells also had a higher expression of the antiapoptotic family member BCL2L1 (also known as Bcl-XL) (log 2 FC = 0.13, adjusted P << 0.0001), of the viral sensor IFIH1 (MDA5) (log 2 FC = 0.97, adjusted P << 0.0001), and of the inhibitory variant HLA-E (log 2 FC = 0.76, adjusted P << 0.0001).…”
Section: Scrna-seq Of Ifn-treated Ipsc-derived Islet-like Cells Show...mentioning
confidence: 68%
“…As expected, PDX1 expression was higher in -like cells, while Aristaless Related Homeobox (ARX), a transcription factor specifically expressed in glucagon-producing  cells, was much higher in -like cells. -Like cells had higher expression of the proapoptotic ER stress marker DDIT3 (also known as CHOP) [log 2 fold change (log 2 FC) = 2.20, adjusted P << 0.0001] and also XBP1 (log 2 FC = 0.70, adjusted P << 0.0001) [in line with (32)], while -like cells showed higher expression of the protective chaperone HSPA5 (also known as BiP) (log 2 FC = 0.13, adjusted P << 0.0001). Compared to -like cells, -like cells also had a higher expression of the antiapoptotic family member BCL2L1 (also known as Bcl-XL) (log 2 FC = 0.13, adjusted P << 0.0001), of the viral sensor IFIH1 (MDA5) (log 2 FC = 0.97, adjusted P << 0.0001), and of the inhibitory variant HLA-E (log 2 FC = 0.76, adjusted P << 0.0001).…”
Section: Scrna-seq Of Ifn-treated Ipsc-derived Islet-like Cells Show...mentioning
confidence: 68%
“…For some cell types, pro-inflammatory cytokines such as IL-1β in combination with IFN-γ, as well as TNF-α have been shown to induce cytokine-dependent apoptosis [ 41 , 42 ]. These cytokines also increase the sensitivity of hepatocytes to Fas-induced cell death [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in apoptosis and decline in expression of maturation markers for the SA-engineered scaffold condition is consistent with the findings by others for β-cells and hPSC derived β-cells. 27,50,61 Moreover, SA-FasL-engineered scaffolds-maintained differentiation state and reduced caspase-dependent apoptosis. An analysis of cytokine expression within the conditioned media did not provide a simple mechanistic explanation for the decreased apoptosis with SA-FasL conditioned media compared to the control conditioned Our studies identified increased expression of one pro-inflammatory factor, one anti-inflammatory factor, and undetectable levels of several other cytokines that are pro-or anti-inflammatory.…”
Section: ■ Discussionmentioning
confidence: 95%
“…Cytokines such as TNF-a, IFN, IL-6, and CXCL8 38 directly act on islet derived β-cells to induce apoptosis, 51,55−57 with TNF-α being one of the primary factors that are detrimental to β-cells. Apoptosis occurs through activated caspase-dependent apoptosis via the extrinsic and intrinsic apoptosis signaling pathways, 50,58 with activation of stress-induced kinases IKKβ and JNK, and initiation of a signaling cascade involving NFκB and NLRP3 in β-cells. 51,55−57 Inflammation and the associated proinflammatory factors within the in vivo microenvironment is expected to reduce insulin secretion and delay maturation of the hPSC derived β-cells.…”
Section: ■ Discussionmentioning
confidence: 99%